Innovation Design the Text to Braille Based Technology in Computer Vision - Adi Pratama Putra; Muhamad Khoirul Anam; Muhammad Zainal Roisul Amin; Rezki Nalandari; Adi Mulyadi; Harwanti Noviandari (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
This paper discusses the design of assistive technological innovations for writing text on books onto braille boards and computer vision-based sound. So far, programs for converting writing into braille are still very difficult to find, changing from written form to sound. The design for the development of assistive technology that will be produced refers to an analysis of the current needs for blind students, where these students can only read Braille, not Latin. Broadly speaking, this research is image processing of Latin letters with board braille output and sound using a camera scanner with an algorithm processing on the Raspberry Pi system, so that scripts with Latin characters can be enjoyed by the blind.